ANALISIS PERBEDAAN KINERJA KEUANGAN SEBELUM DAN SESUDAH MERGER DAN AKUISISI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ali, Karnila (Derivatif : Jurnal Manajemen, 2020)
In general, the purpose of conducting mergers and acquisitions is to obtain synergy or added value. However, mergers and acquisitions by companies do not always produce added value for the company, often failure or deteriorating company performance occurs after the company makes mergers and acquisitions. The purpose of this study is to differ the financial performance of companies before and after mergers and acquisitions based on financial ratio assessments.The method used in this research is quantitative descriptive method. This type of research is quantitative research with the object of research is the financial performance before and after mergers and acquisitions in companies in Indonesia which are listed on the Indonesia Stock Exchange in 2015-2018. Data collection techniques using documentation. The analytical tool used is to use an analysis of the company's financial statements.The results showed that based on financial ratios, namely CR (Current Ratio), DER (Debt to Equity Ratio), ROE (Return on Equity), ROA (Return on Assets), NPM (Net Profit Margin), and Earning Per Share (EPS ) it can be seen that the actions of mergers and acquisitions have no effect on the company's financial performance within 1 year after the merger and acquisition.Keywords: CR (Current Ratio), DER (Debt to Equity Ratio), ROE (Return on Equity), ROA (Return on Assets), NPM (Net Profit Margin), and Earning Per Share (EPS)